Pengaruh Promosi, Harga dan Citra Merek Terhadap Minat Pemakaian Jasa Fotografi - Mas Totok Illa; Septian Adi Nugraha (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2020)
This research was conducted to test the influence of promotion, price and brand image towards the use of service interest Bamita Java Studio Wagir Malang Regency, to know the customer's response to the promotion, price and brand image of interest in service usage in Bamita Java Studio, and to know how much the influence of promotion, price and brand image of interest in the use of services in Bamita Java Studio. The research used is a quantitative with a survey method. This type of research is explanatory. The population in this research is the consumer of Bamita Java Studio who visited within three months from October to December 2019. The data used is data managed by the Administration section of Bamita Java Studio. Sampling techniques used are accidental sampling. The analytical techniques used in this study are multiple linear regression to obtain a thorough picture of the relationship between the Variabel or the other variables. The t test result indicates that the significance value of each free variable is 0.036 for the promotion variable, 0.000 for the price Variable, and 0.004 for the brand image variable. While T values can be said to be significant when (T < 0.05), and from the statistical test results, the promotion variable has a signification value T 0.036 which means < 0.05, then Ha in the received and Ho rejected, so it can be said that the promotional Vatican is positive and significant to the interest in the service usage, for the price variable has a significance value of 0.000, which means that the Ha 0.05 Ho Interest in using the service, while the brand image variable has a signification value of T 0.004 meaning < 0.05, then Ha in the received and Ho rejected, and also can be said that the brand's variable effect is positive and significant to the interest in service usage.